2 Edw. 3, c. 3 (1328) (Eng.) - (:unkn) unknown (General Publisher)
Statute of Northhampton; forbade any person to come before the King's justices or ministers "with force and arms," "nor bring no force in affray of the peace, nor to go nor ride armed" in fairs, markets, before the justices and ministers, "nor in no part elsewhere…."
--
Keywords: CARRY - CERTAIN PUBLIC PLACES